SUSAN LARSON (ed.) - Comfort and Domestic Space in Modern Spain - Zubiaure, Maite (ZARCH, 2025)
SUSAN LARSON (ed.)Comfort and Domestic Space in Modern SpainUniversity of Toronto Press, Toronto, 392 pp. Tapa dura. 100.00 $Idioma: inglés ISBN-10‏: ‎ 1487529104ISBN-13: ‎ 978-1487529109